Penerapan Metode Economical Order Quantity Untuk Sistem Stok Barang Penggudangan dengan menggunakan teknologi Radio Frequency Identification - Istanto, Teddy (Universitas Diponegoro, 2017)
The application of Economical Order Quantity method to stock warehouse system by using Radio Frequency Identification technology can provide information that can minimize stock availability in real time.Â The research aims to develop the stock system using the methods of Economical Order Quantity, Reorder Point and Radio Frequency Identification technology. Computation of Economical Order Quantity is used per month with variables covering amount of raw material, ordering cost and storage cost. Reorder Point computation using lead time variable, raw material usage and safety stock. Safety stock is used if there is a delay in delivery of goods from suppliers, so it does not run out of raw materials and the company can still operate. The inventory data is obtained from transactions of incoming and outgoing goods which are recorded automatically when passing through Radio Frequency Identification reader. The computation of Economical Order Quantity, Reorder Point produces safety stock as output stock system. With the stock of goods in accordance with the fulfillment of Safety stock, then there is no delay in the delivery of goods from suppliers, so it does not run out of raw materials, after determination of the value of re-ordering.